Let's call quiet quitting what it often is : calibrated contributing : for employees who are rationally matching their effort at work to what they get in return in an increasingly unbalanced system, quiet quitting is not the right term - Detert, James R. (MIT Sloan Management Review, 2023)
When the term quiet quitting is applied to employees whose efforts don't exceed what's in their job descriptions, it fails to recognize the current reality of real wages that have significantly decreased over the past 50 years while executive pay has skyrocketed. The author argues that quiet quitting should be replaced with a different label -- calibrated contributing -- that reflects an employee's rational choice to do the work they're paid for rather than go above and beyond unrewarded.